Tales of Brexits past and present : choices, threats and opportunities in our separation from the EU - Culkin, Nigel; Simmons, Richard E. (Emerald Publishing Limited, 2018)
'Tales of Brexits Past and Present: Understanding the Choices, Threats and Opportunities In Our Separation from the EU'provides a compelling insight into the Brexit process in a uniquely historical context. Looking at previous 'Brexits' under the lens of international risk, the book tackles five specific themes relating to the Brexit result - competition in the global innovation economy, the generational split, the 'left behind' aspirational working and middle classes, the impact on international relations, and popularism in the internet age. By looking to the past, this book will offer insights into what we might expect in the future, providing an engaging narrative that will open the minds of readers to the options, risks and opportunities that could be unmasked in the Brexit process.
Prelims -- Introduction -- Motivation, myth and reality -- Brexit today: the current state of play -- Brexit MK I AD 410 -- Brexit MK II The road from Rome in the 1530's -- Brexit MK III Elizabeth I: the pragmatic problem solver -- The global innovation economy -- The generational divide -- The left behind -- International dimensions -- Popularism and the internet -- Which Brexit this time? -- Appendix 1: The European Union today -- Appendix 2: Could subsidiarity be 'Praemunire' in sheep's clothing? -- Appendix 3: July 2018 Brexit white paper -- Endnotes -- Glossary -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Great Britain -- Foreign economic relations -- History; Great Britain -- Foreign economic relations -- Forecasting; Business & Economics -- General; Economics, finance, business & management